MODEL ISOTERM ADSORPSI LITIUM DARI BRINE WATER, BOGOR MENGGUNAKAN ADSORBEN HYDROUS MANGANESE OXIDE (HMO) - Mhd Yasin Siregar (Metalurgi, 2019)
The latest industrial revolution or fourth generation is driving computer-based automation systems. The development of science and technology in computers increases the demand for the use of secondary Li-ion batteries. Lithium is an important raw material for cathode materials in rechargeable batteries. At present the need for lithium (Li) is increasing very high, due to the wide range of uses as raw material for rechargeable batteries. Until now the main source of lithium comes from brine water and lithium ores such as spodumene. Brine is one of the most important sources of lithium. Brine water from Ciseeng, Bogor contains 50-80 ppm lithium. Adsorption is a fairly good method for recovering lithium from brine. The adsorbent used is the result of acid activation from the precursors with the method of making solid state. Adsorption is done by varying the adsorbent dose 5; 7.5; 10; 12.5; and 15 g / L and adsorption process time 0.5; 1; 2; 3; 4; and 24 hours to determine the percent of adsorption, adsorption selectivity and the type of adsorption that occurs. The highest dose of lithium adsorption was 7.5 g / L with 7.28% lithium adsorption with selectivity values of αLi / Na 0.92 and αLi / K 1.18. Percentage of lithium adsorption with the highest time variation is at 24 hours with lithium adsorption percentage of 15.33% with selectivity values of αLi / Na 2.38 and αLi /K 0.89 at a dose of 7.5 g / L. The adsorption isotherm shows that Li adsorption follows the Freundlich isotherm model because the R2 value is higher than the Langmuir isotherm model, so the adsorption that occurs is physical adsorption (physiosorption) and forms a multilayer layer.